2018
DOI: 10.1590/s1413-41522018161706
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo de melancia no semiárido irrigado com diferentes lâminas de esgoto doméstico tratado

Abstract: RESUMO O objetivo deste trabalho foi avaliar a viabilidade agronômica do uso de esgoto doméstico tratado em reator anaeróbio para o cultivo de melancia tipo Crimson Sweet. Em estudo de campo no Sertão Pernambucano, avaliou-se a aplicação de quatro lâminas de irrigação por meio do sistema de gotejamento. Foram avaliadas as lâminas de 50, 75, 100 e 125% baseadas nos resultados da evapotranspiração e nas exigências do sistema de irrigação adotado. A caracterização do efluente tratado indicou conformidade com as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
6
0
4
Order By: Relevance
“…Evaluations of the efficiency of sewage treatment systems in several Brazilian states confirm this range, with average values of 25 to 150 mg L -1 (GONÇALVES, et al, 2015;QUEIROZ;QUEIROZ;ARAGÃO, 2015). Regarding the agricultural application, effluents with concentrations above 65 mg L -1 were applied as fertigation to crops in the semiarid region and did not interfere with their growth (RIBEIRO et al, 2012;SALGADO et al, 2018).…”
Section: Domesticmentioning
confidence: 94%
See 1 more Smart Citation
“…Evaluations of the efficiency of sewage treatment systems in several Brazilian states confirm this range, with average values of 25 to 150 mg L -1 (GONÇALVES, et al, 2015;QUEIROZ;QUEIROZ;ARAGÃO, 2015). Regarding the agricultural application, effluents with concentrations above 65 mg L -1 were applied as fertigation to crops in the semiarid region and did not interfere with their growth (RIBEIRO et al, 2012;SALGADO et al, 2018).…”
Section: Domesticmentioning
confidence: 94%
“…Several studies present non-quantifiable values of metals. Andrade Filho et al (2013), Oliveira et al (2014), Queiroz, Queiroz andAragão (2015), and Salgado et al (2018) evaluated copper, iron, manganese, and zinc contents in sewages used for irrigation in the Brazilian semiarid region and found 0.02 to 0.45 mg L -1 (Cu), 0.18 to 2.20 mg L -1 (Fe), 0.07 to 0.15 mg L -1 (Mn), and 0.05 to 1.25 mg L -1 (Zn), with no effect on the development of the crops.…”
Section: Domesticmentioning
confidence: 98%
“…Several researches have pointed out the possibility of irrigation of several plant species with poor quality water, being a widely studied practice and recommended by several researchers and water managers. From a nutritional point of view, studies have shown positive effects of irrigation with high salinity water, such as sewage, on the production and productivity of vegetables, proving the fertilizing effect of wastewater in numerous studies and in various cultures such as sunflower (Santos Júnior et al, 2014;Oliveira et al, 2017), pepper (Silva et al, 2019), melon (Costa et al, 2014), corn (Malafaia et al, 2016), tomato (Jorge et al ., 2017) and watermelon (Salgado et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Maize cultivation in the Brazilian semi-arid region stands out for its economic importance in family farming, with a high contrast in yield due mainly to climatic conditions, irrigation and fertilization practices [1,2]. Due to water scarcity in the region, the use of wastewater for irrigation is a promising alternative for reducing the consumption of higher-quality water and hence reducing environmental How to cite: Almeida, T.A.B., M ontenegro, A.A.A., de Carvalho, A.A. and Tabosa, J.N., Soil and crop spatial variability in maize irrigated with domestic effluent.…”
Section: Introductionmentioning
confidence: 99%